A Noninvasive Method for Quantifying Cerebral Metabolic Rate of Oxygen by Hybrid PET/MRI: Validation in a Porcine Model - Narciso Lucas; Ssali Tracy; Liu Linshan; Biernaski Heather; Butler John; Morrison Laura; Hadway Jennifer; Corsaut Jeffrey; Hicks Justin W; Langham Michael C; Wehrli Felix W; Iida Hidehiro; et al. (Society of Nuclear Medicine, 2022)
The gold standard for imaging the cerebral metabolic rate of oxygen (CMRO2) is positron emission tomography (PET); however, it is an invasive and complex procedure that also requires correction for recirculating 15O-H2O and the blood-borne activity. We propose a noninvasive reference-based hybrid PET/magnetic resonance imaging (MRI) method that uses functional MRI techniques to calibrate 15O-O2-PET data. Here, PET/MR imaging of oxidative metabolism (PMROx) was validated in an animal model by comparison to PET-alone measurements. Additionally, we investigated if the MRI-perfusion technique arterial spin labelling (ASL) could be used to further simplify PMROx by replacing 15O-H2O-PET, and if the PMROx was sensitive to anesthetics-induced changes in metabolism. Methods: 15O-H2O and 15O-O2 PET data were acquired in a hybrid PET/MR scanner (3 T Siemens Biograph mMR), together with simultaneous functional MRI (OxFlow and ASL), from juvenile pigs (n = 9). Animals were anesthetized with 3% isoflurane and 6 mL/kg/h propofol for the validation experiments and arterial sampling was performed for PET-alone measurements. PMROx estimates were obtained using whole-brain (WB) CMRO2 from OxFlow and local cerebral blood flow (CBF) from either noninvasive 15O-H2O-PET or ASL (PMROxASL). Changes in metabolism were investigated by increasing the propofol infusion to 20 mL/kg/h. Results: Good agreement and correlation were observed between regional CMRO2 measurements from PMROx and PET-alone. No significant differences were found between OxFlow and PET-only measurements of WB oxygen extraction fraction (0.30 ± 0.09 and 0.31 ± 0.09) and CBF (54.1 ± 16.7 and 56.6 ± 21.0 mL/100 g/min), or between PMROx and PET-only CMRO2 estimates (1.89 ± 0.16 and 1.81 ± 0.10 mLO2/100 g/min). Moreover, PMROx and PMROxASL were sensitive to propofol-induced reduction in CMRO2 Conclusion: This study provides initial validation of a noninvasive PET/MRI technique that circumvents many of the complexities of PET CMRO2 imaging. PMROx does not require arterial sampling and has the potential to reduce PET imaging to 15O-O2 only; however, future validation involving human participants are required.